A novel genetic variant potentially altering the expression of MANBA in the cerebellum associated with attention deficit hyperactivity disorder in Han Chinese children. (9th August 2022) - Chen, Xinzhen; Yao, Ting; Cai, Jinliang; Zhang, Qi; Li, Shanyawen; Li, Huiru; Fu, Xihang; Wu, Jing
Abstract: Objectives: To obtain additional insight into the genetic factors of attention deficit hyperactivity disorder (ADHD). Methods: First, we performed a transcriptome-wide association study (TWAS) integrating human cerebellum-specific variant-expression/splicing correlations to identify ADHD susceptibility genes. Then, the associations between expression/splicing quantitative trait loci (eQTLs/sQTLs) of the transcriptome-wide significant genes and ADHD were observed in a case-control study of Han Chinese children. Furthermore, dual luciferase reporter gene assays were performed to validate the regulatory function of ADHD risk variants. Additionally, the transcription level of target genes in blood was detected by real-time quantitative polymerase chain reaction (RT-qPCR) assay. Results: TWAS identified that the genetically regulated expression of MANBA in the cerebellum was significantly associated with ADHD risk. Furthermore, we observed a higher risk of ADHD and more severe clinical symptoms in subjects harbouring heterozygous (TC) or mutant homozygous (TT) genotypes of MANBA rs1054037 than CC carriers. The dual luciferase reporter gene assay revealed that the mutation of rs1054037(C > T) potentially upregulated MANBA expression by eliminating the binding site for hsa-miR-5591-3P. Finally, RT-qPCR showed that MANBA expression in blood samples of patients was significantly higher than that of controls. Conclusions: Taken together, these results suggest a role of MANBA in the development of ADHD.